Protection of Women's Rights in the Framework of the Welfare State (Comparative Study of Indonesia and the UK) - Mohammad Khoerul Khusna (Asian Journal of Law and Humanity, 2023)
The welfare state is closely related to the protection of the rights of every citizen, in this case such as the protection of women's rights. However, in its implementation there is often a lack of compliance with existing regulations, so the research entitled Protection of Women's Rights in the Framework of a Welfare State (Comparative Study of Indonesia and England, The focus of this research is to describe the protection of women's rights within the framework of a welfare state (comparative study of Indonesia and the UK). The type of research is normative juridical literature research with an approach that examines theories, concepts, and examines laws and regulations related to the research. this or a statutory approach. Normative juridical research is legal research that places law as a building system of norms.This research describes the protection of women's rights within the framework of a welfare state with the results of the research showing that the comparison of protection of women's rights in Indonesia and England is based on comparative legal theory, Article 281 paragraph (4) of the 1945 Constitution of the Republic of Indonesia and Article 71 of the Law. -Human Rights Law no. 39 recognizes constitutional protection. According to CEDAW, the principles of the state's duties include guaranteeing women's human rights through laws and policies, and in addition, the state must not only guarantee but also implement women's rights. The state must not only regulate the public sector, but also the activities of people and institutions in the private sector, namely the family. Meanwhile, this thematic shadow report highlights violence against women in England across the UK. and Guarantee of Protection of Women's Rights in Both Countries Within the Framework of a Welfare State, namely Based on this theory, the legal protection of women's human rights in the country in the form of guarantees of economic, social and political rights, and which was previously a private matter that should not be regulated by the state, is now a task state to regulate it, which is now in the realm of public law. The Law on the Elimination of Domestic Violence Number 23 of 2004 (PKDRT) provides a new formulation which states that the state can also intervene in private life. At the same time, in the UK, the Domestic Violence, Crime and Victims Act 2004 was an attempt by the government to intervene into family life. coordinating policy development and implementation across departments is welcomed in the UK.